IL‐34 in hepatoblastoma cells potentially promote tumor progression via autocrine and paracrine mechanisms - Tomoaki Irie; Daiki Yoshii; Yoshihiro Komohara; Yukio Fujiwara; Masashi Kadohisa; Masaki Honda; Shinya Suzu; Toshiharu Matsuura; Kenichi Kohashi; Yoshinao Oda; Taizo Hibi (Cancer Medicine, 2022)
Abstract Hepatoblastoma is the most common pediatric liver tumor, but little research has been done on the role of macrophages in hepatoblastoma. The purpose of this study was to gain insight into potential roles for macrophages in hepatoblastoma. Paraffin‐embedded specimens from 56 patients who underwent surgical resection were examined with immunohistochemical staining for the macrophage‐specific markers, Iba1 and CD163. Significant differences were seen among histological subtypes. Significantly increased numbers of macrophages were detected in embryonal components compared to fetal components in the mixed epithelial type. In vitro studies using human monocyte‐derived macrophages and two hepatoblastoma cell lines (HepG2 and Huh6) were performed. Conditioned medium from these cell lines induced increased CD163 expression in macrophages. Direct co‐culture with macrophages induced tumor cell proliferation via induction of protumor cytokine secretion from macrophages. Direct co‐culture with macrophages also induced interleukin (IL)‐34 overexpression by Huh6 cells via Brd4 signaling. IL‐34 overexpression promoted tumor cell proliferation and chemoresistance. High IL‐34 and Brd4 expression was detected in embryonal components, which have potentially higher proliferation activity than fetal components. In conclusion, IL‐34 expression in embryonal components may induce macrophage chemotaxis in a paracrine manner, and tumor cell proliferation and chemoresistance in an autocrine manner. IL‐34 is a potential therapeutic target for hepatoblastoma.